Investigation of the Supply Chain Strategy Effects on Substantive Legal Framework and Problems of Iraqi Local Authorities` Activity in the Social Sphere - Evgeny Batyrovich Sultanov; Jaafar Haser Abdulrida (International Journal of Supply Chain Management, 2019)
This article considers the legal norms regulating the activities of local governments in the field of social services at the federal, regional and municipal levels of government, the activities of municipal social services to provide social assistance and support and issues relating to the separation of powers between state authorities and local governments in social services. In recent years, many social problems have arisen or worsened, resulting in a decline in the population of Iraq. According to the latest data, August - December 2009, the number of Iraqis decreased by 30.4 thousand people. In comparison with the same months last year, Iraqis have died more than 11.5 thousand. Across the country, the number of deaths on the number of births was 2.6 times. Therefore, an active local social policy in the field of social services is one of the most important tasks of municipal development. It is at the municipal level that it is easier to identify social problems, determine the circle of people in need of social assistance, develop the system of social services, improve the quality of social services provided, thereby increasing the efficiency of social services at the local level.